2023
DOI: 10.1038/s43856-023-00257-1
|View full text |Cite
|
Sign up to set email alerts
|

Estimating COVID-19 vaccine uptake and its drivers among migrants, homeless and precariously housed people in France

Abstract: Background Migrants, people experiencing homelessness (PEH), or precariously housed (PH) are at high risk for COVID-19 infection, hospitalization, and death from COVID-19. However, while data on COVID-19 vaccine uptake in these populations are available in the USA, Canada, and Denmark, we are lacking, to the best of our knowledge, data from France. Methods In late 2021, we carried out a cross-sectional survey to determine COVID-19 vaccine coverage … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The second study investigated vaccination coverage after one dose and found a negative effect in the group with chronic diseases [10]. In France, similar findings among socially vulnerable groups in Paris and Marseille have been described [29].…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The second study investigated vaccination coverage after one dose and found a negative effect in the group with chronic diseases [10]. In France, similar findings among socially vulnerable groups in Paris and Marseille have been described [29].…”
Section: Discussionmentioning
confidence: 69%
“…The second study investigated vaccination coverage after one dose and found a negative effect in the group with chronic diseases [10]. In France, similar findings among socially vulnerable groups in Paris and Marseille have been described [29]. In the Swedish setting, socioeconomic differences regarding vaccination coverage, without linkage to medical diagnosis, have been previously reported [8, 9].…”
Section: Discussionmentioning
confidence: 86%
“…With regard to COVID-19, a qualitative interview study with recently arrived migrants and refugees in the United Kingdom reported that 72% of participants were hesitant to uptake a COVID-19 vaccine before the start of large-scale vaccination campaigns [ 43 ]. A recent French study reported a significantly lower COVID-19 vaccination rate among precariously housed and collectively accommodated migrants than among the general French population [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the most critical point is targeting effective prevention strategies including COVID-19 vaccination efforts among people experiencing homelessness. In France, COVID-19 vaccination strategy targeting people who are homeless was implemented in May 2021, including management of vaccination centers for marginalized population, sensitization, mobile vaccination teams, and physical accompaniment to vaccination centers ( 54 ).…”
Section: Discussionmentioning
confidence: 99%